Evaluasi Program Pelayanan Kesehatan Ramah Remaja (PKRR) Dalam Pendidikan Kesehatan Reproduksi Remaja Awal - Grhasta Dian Perestroika; Dewi Andang Prastika; Nawang Swastika Raras; Rosiana Alfa Risqi; Riadini Wahyu Utami; Sinta Rosita Sari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Introduction: In Indonesia, one of the efforts to prevent risky sexual behavior is to providereproductive health education among adolescents. One of the programs that collaborate withschools in providing reproductive health education is the pelayanan kesehatan ramah remaja(PKRR) organized by the Dinas Kesehatan. However, studies on the evaluation of the PKRRprogram among early adolescents in Indonesia have not been widely studied. Methods: A qualitative study was conducted on 14 early adolescents, 1 provider and 1practitioner PKRR in November 2019-February 2020. Data were collected by Focused GroupDiscussion (FGD) and semi-structured interviews using the RE-AIM framework. Data wasanalyzed using Stevick-Colaizzi-Keen method in Nvivo 12 software.Result: The advantage of this program is that it can reach the target of early adolescents inthe school. One of the weaknesses of this program is the limited time when socialization wascarried out in schools. In addition, another weakness is the implementation at the communitylevel, in the form of Posyandu remaja and counseling. It is difficult to reach early adolescentsin the community level, because there is a feeling of shame to come to the place of services.Conclusion: This evaluation succeeded in revealing the needs of adolescents forreproductive health information, including the desire of adolescents to better understandreproductive health. The implication of this study is that there is a need for improvement in theimplementation of the PKRR program. Improvements include the addition of comprehensivesexual education, cross-sectoral collaboration and the regeneration of young implementersfor better implementation.Keywords: Evaluation, Early Adolescents, PKRR, Reproductive Health Education, RE-AIM.